2016
DOI: 10.1088/1748-0221/11/03/c03006
|View full text |Cite
|
Sign up to set email alerts
|

Use of micro computed-tomography and 3D printing for reverse engineering of mouse embryo nasal capsule

Abstract: Imaging of increasingly complex cartilage in vertebrate embryos is one of the key tasks of developmental biology. This is especially important to study shape-organizing processes during initial skeletal formation and growth. Advanced imaging techniques that are reflecting biological needs give a powerful impulse to push the boundaries of biological visualization. Recently, techniques for contrasting tissues and organs have improved considerably, extending traditional 2D imaging approaches to 3D. X-ray micro co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 19 publications
(32 reference statements)
0
39
0
1
Order By: Relevance
“…Analysis of the early development of the chondrocranium and its association with the forming skull has been hampered by the difficulty in visualizing embryonic cartilage in 3D. The recent Kaucka and Tesařová protocols demonstrated that PTA staining could successfully be used to visualize and analyze the chondrocranium, both in its entirety and with specific focus on the nasal capsule, in embryonic mice . Our expansion of the Kaucka and Tesařová protocols allows the segmentation of bone from the same PTA‐enhanced microCT scan, allowing the creation of high‐resolution 3D models of the forming dermatocranium and chondrocranium (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the early development of the chondrocranium and its association with the forming skull has been hampered by the difficulty in visualizing embryonic cartilage in 3D. The recent Kaucka and Tesařová protocols demonstrated that PTA staining could successfully be used to visualize and analyze the chondrocranium, both in its entirety and with specific focus on the nasal capsule, in embryonic mice . Our expansion of the Kaucka and Tesařová protocols allows the segmentation of bone from the same PTA‐enhanced microCT scan, allowing the creation of high‐resolution 3D models of the forming dermatocranium and chondrocranium (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the majority of published protocols provide only minimal details, requiring extensive experimentation to reach an optimized protocol, particularly if using a different model organism, specimen age, or tissue type. One research group has published detailed PTA protocols for use in embryonic mice from E12.5 to 18.5 . The Kaucka and Tesařová protocols added several significant steps to Metscher's original PTA staining method: a slow graded ethanol and methanol dehydration series, different suggested staining times for several ages of embryonic mice, and a final graded methanol rehydration series.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a remedy, 3D virtual models can now also be made accessible to dental students as custom-made and scaled physical objects through additive manufacturing (AM), thus providing students with a genuinely 3D interpretive experience [106,107]. AM is a process by which different types of material can be added layer-by-layer to produce a 3D object [108] and is increasingly being used in the life sciences [109][110][111].…”
Section: Additive Manufacturing Of Three-dimensional Human Tooth Modelsmentioning
confidence: 99%